2022
DOI: 10.1149/2162-8777/ac9f66
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ferric Nitrate on Semi-Insulating 4H-SiC (0001) Chemical Mechanical Polishing

Abstract: Semi-insulating 4H-SiC(0001) has high hardness and high chemical inertness, making it difficult to obtain high material removal rates during chemical mechanical polishing (CMP). In this paper, the role of chemical additive ferric nitrate in semi-insulating 4H-SiC(0001) CMP with α-alumina as abrasive and KMnO4 as oxidant is discussed. The results showed that 0.5 wt% ferric nitrate can increase the removal rate of semi-insulating 4H-SiC(0001) by 34%, while the semi-insulating 4H-SiC(0001) surface roughness Ra wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…He et al 17 used the slurry with SiO 2 and TiO 2 in photocatalysis-assisted chemical mechanical polishing of 4H-SiC, but the polished surface had obvious swallow scratches and the roughness Ra of 0.247 nm. Wang et al 18 reported the Al 2 O 3 -KMnO 4 -based slurry combined with the catalyst ferric nitrate to polish SiC could increase the removal rate and reduce the roughness Ra to 0.110 nm.…”
mentioning
confidence: 99%
“…He et al 17 used the slurry with SiO 2 and TiO 2 in photocatalysis-assisted chemical mechanical polishing of 4H-SiC, but the polished surface had obvious swallow scratches and the roughness Ra of 0.247 nm. Wang et al 18 reported the Al 2 O 3 -KMnO 4 -based slurry combined with the catalyst ferric nitrate to polish SiC could increase the removal rate and reduce the roughness Ra to 0.110 nm.…”
mentioning
confidence: 99%